The religiosity of Hijrah adolescence in Muslimah Aceh Fillah Community Aceh Tamiang Indonesia - Nadya Afriyanti; Dedy Surya (INSPIRA, 2020)
In the influx of hedonism and consumptive culture due to the development of communication and information technology, extraordinary hijrah flows from the young generation of Indonesia. This study aims at the religiosity of adolescents experienced by hijrah adolescents through 5 dimensions of religiosity: experiential, ritualistic, ideological, intellectual, and consequential. This study involved 5 Muslimah Aceh Fillah members selected by purposive sampling techniques using a qualitative approach. In-depth interview techniques and participatory observations obtained the data. In addition to engaging its members, the researchers also took parental data from the study subjects to get a comprehensive picture. Then, the data is analyzed through 3 stages: data reduction, data presentation, and conclusion. The results showed that the religiosity of hijrah adolescents is expressed in various dimensions. The most significant change felt by community members is thought in an intellectual dimension that implies an improvement in the other aspect of religiosity.